2016
DOI: 10.1038/cddis.2016.361
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of microRNA-27b-3p enhances tamoxifen resistance in breast cancer by increasing NR5A2 and CREB1 expression

Abstract: Estrogen-dependent breast cancer is often treated with the aromatase inhibitors or estrogen receptor (ER) antagonists. Tamoxifen as a major ER antagonist is usually used to treat those patients with ERα-positive breast cancer. However, a majority of patients with ERα positive fail to respond to tamoxifen due to the presence of intrinsic or acquired resistance to the drug. Altered expression and functions of microRNAs (miRNAs) have been reportedly associated with tamoxifen resistance. In this study, we investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 50 publications
5
53
0
Order By: Relevance
“…Qu et al showed that miR-150 significantly enhanced EMT signaling by regulating the CREB1 expression in CRC cells [36]. He et al demonstrated that miR-27b-3p directly targeted and inhibited the expression of CREB1, which played a key role in the resistance to tamoxifen in breast cancer cells [37]. Our results showed that down-regulation of CREB1 inhibited cell migration, invasion and induced cell apoptosis.…”
Section: Discussionsupporting
confidence: 60%
“…Qu et al showed that miR-150 significantly enhanced EMT signaling by regulating the CREB1 expression in CRC cells [36]. He et al demonstrated that miR-27b-3p directly targeted and inhibited the expression of CREB1, which played a key role in the resistance to tamoxifen in breast cancer cells [37]. Our results showed that down-regulation of CREB1 inhibited cell migration, invasion and induced cell apoptosis.…”
Section: Discussionsupporting
confidence: 60%
“…20,21,27,28 Therefore, we further investigated whether miR-506 could directly regulate CREB1 in ovarian cancer. 20,21,27,28 Therefore, we further investigated whether miR-506 could directly regulate CREB1 in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-148a and miR-152 were able to reduce tamoxifen resistance in ER-positive breast cancer via downregulating ALCAM [10]. Downregulation of microRNA-27b-3p enhanced tamoxifen resistance in breast cancer by increasing NR5A2 and CREB1 expression [8]. Therefore, miRNAs may be a novel therapeutic approach to sensitizing and suppressing the growth of tamoxifen-resistant breast tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that abnormal expression of miRNAs plays an important role in tamoxifen resistance [2,[7][8][9][10]. MiRNAs belong to a novel class of regulatory determinants which are small non-coding RNAs, about 20-23 nucleotides in length.…”
Section: Introductionmentioning
confidence: 99%